The Behavior and Determinants of Stock Market Index in Indonesia - Wuryandani, Gantiah (The Indonesian Capital Market Review, 2011)
This research proves that the movement of Stock Market Index (JSX) in Indonesia does not follow random walk. Therefore, certain variables in inancial market inluence the movement of JSX. VECM and ECM testings show that regional index in ASEAN countries and Hongkong as well as exchange rate signiicantly affect JSX movement. This indicates a strong contagious effect of the stock market in Asia on the Indonesian stock market, which joined the exchange rate effects concurrently. On the other hand, monetary policy through Bank Indonesia rate (BI rate) less strongly affects the movement of JSX, albeit signiicant. Implicitly, this indicates that monetary policy transmission path through the stock market is still weak. Given the limited authority to intervene other country's stock market, the policy implication of this study suggests the authorities to maintain exchange rate stability. This especially relates to policies for speculative capital lows. It is the time for the authorities to establish policies to improve the effectiveness and eficiency of inancial markets as inancial intermediation